Optic Tract Shrinkage Limits Visual Restoration After Occipital Stroke. Issue 11 (November 2021) - Fahrenthold, Berkeley K.; Cavanaugh, Matthew R.; Jang, Subin; Murphy, Allison J.; Ajina, Sara; Bridge, Holly; Huxlin, Krystel R.
Abstract : Background and Purpose: Damage to the adult primary visual cortex (V1) causes vision loss in the contralateral visual hemifield, initiating a process of trans-synaptic retrograde degeneration. The present study examined functional implications of this process, asking if degeneration impacted the amount of visual recovery attainable from visual restoration training in chronic patients, and if restoration training impacted optic tract (OT) shrinkage. Methods: Magnetic resonance imaging was used to measure OT volumes bilaterally in 36 patients with unilateral occipital stroke. From OT volumes, we computed laterality indices (LI), estimating the stroke-induced OT shrinkage in each case. A subset of these chronic patients (n=14, 13±6 months poststroke) underwent an average of nearly 1 year of daily visual restoration training, which repeatedly stimulated vision in their blind field. The amount of visual field recovery was quantified using Humphrey perimetry, and post training magnetic resonance imaging was used to assess the impact of training on OT shrinkage. Results: OT LI was correlated with time since stroke: it was close to 0 (no measurable OT shrinkage) in subacute participants (<6 months poststroke) while chronic participants (>6 months poststroke) exhibited LI >0, but with significant variability. Visual training did not systematically alter LI, but chronic patients with baseline LI≈0 (no OT shrinkage) exhibited greater visual field recovery than those with LI>0. Conclusions: Unilateral OT shrinkage becomes detectable with magnetic resonance imaging by ≈7 months poststroke, albeit with significant interindividual variability. Although visual restoration training did not alter the amount of degeneration already sustained, OT shrinkage appeared to serve as a biomarker of the potential for training-induced visual recovery in chronic cortically blind patients. Abstract : Supplemental Digital Content is available in the text.